Induction of labour using prostaglandin E2 as an inpatient versus balloon catheter as an outpatient: a multicentre randomised controlled trial. (17th December 2019) - Beckmann, M; Gibbons, K; Flenady, V; Kumar, S
Abstract : Objective: To compare clinical outcomes following induction of labour (IOL) using a balloon catheter and going home, versus prostaglandin (PG) as an inpatient. Design: Randomised controlled trial. Setting: Eight Australian maternity hospitals. Population: Women with uncomplicated term singleton pregnancies undergoing IOL for low‐risk indications including post‐term, advanced maternal age and 'social' reasons. Methods: Between September 2015 and October 2018, 347 women were randomised to a balloon outpatient group and 348 to a PG inpatient group. The PG group received Dinoprostone, either 2 mg gel or 10 mg controlled‐release tape. The balloon group had a double‐balloon catheter inserted and went home. Main outcome measures: The primary outcome was a composite neonatal measure comprising nursery admission, intubation/cardiac compressions, acidaemia, hypoxic ischaemic encephalopathy, seizure, infection, pulmonary hypertension, stillbirth or death. Clinical and process outcomes are reported. Results: There were no statistically significant differences in the primary outcome comparing balloon with PG (18.6% versus 25.8%; relative risk = 0.77, 95% CI 0.51–1.02; P  = 0.070), cord arterial pH <7.10 (3.5% versus 9.2%; P  = 0.072), nursery admissions (12.6% versus 15.5%; P  = 0.379), neonatal antibiotic use (12.1% versus 17.6%; P  = 0.103), or mode of birth. Nulliparous women in the balloon group had lower rates of the primary outcome (20.4% versus 31.0%; P  = 0.032); Parous women were less likely to have an unassisted vaginal birth (77.6% versus 92.3%; P  = 0.045). Conclusions: Balloon catheters may be a superior method of cervical priming for nulliparous women, whereas this may not be the case for parous women. It is feasible that nulliparous women go home after commencing balloon catheter IOL, and the likelihood of adverse outcomes is low. Tweetable abstract: Multicentre trial shows outpatient induction using balloon catheter is safe and feasible for nulliparous women. Tweetable abstract: Multicentre trial shows outpatient induction using balloon catheter is safe and feasible for nulliparous women.